(untitled) (Journal of Asian Development Studies, 2024)
English is recognized as a global communication medium in business, technology, and education. In Pakistan, both Urdu (L1) and English (L2) are used as mediums of instruction, with English predominantly used in Higher Education Institutions (HEIs). Students from diverse linguistic backgrounds are enrolled in HEIs’ business communication courses, where they often encounter challenges in learning. Though code-switching is increasingly utilized as an instructional strategy in English as a Second Language (ESL) contexts, its use as a pedagogical tool in business communication courses in HEIs has yet to be fully recognized. This study aims to explore the perspectives of faculty members and students about code[1]switching as an instructional strategy in business communication courses. A quantitative approach was employed, utilizing a structured questionnaire to collect data from faculty (n = 14) and students (n = 271) at a private-sector university in Karachi. Data analysis was conducted through SPSS. The study reveals that faculty and students hold positive views on using code-switching in business communication courses. However, the study indicates substantial differences in perspectives and varying degrees of agreement or disagreement. Students overwhelmingly support using first language (L1) in the classroom, with 75.6% advocating for it, compared to only 57.2% of faculty. This disparity highlights a potential gap in understanding the benefits that students associate with L1 usage. The study suggests that incorporating code-switching as an instructional strategy can contribute to an inclusive classroom environment, enhancing communication and learning in diverse linguistic settings.